Strategi Pengembangan Usaha Industri Gula Merah Tebu di Kabupaten Tulungagung Provinsi Jawa Timur - RIFA’I, ACHMAD; SUDARMA, I MADE; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.3, Juli 2019, 2019)
The Brown Cane Sugar Industry Business Development Strategy in Tulungagung East Java Province The brown cane sugar industry in Tulungagung is a home industry that is owned by individuals and has many obstacles to run. This research aims to analyze the business feasibility based on the income and BEP (Break Even Point) and to formulate a business development strategy for the sugar cane brown sugar business. This study uses data analysis methods in the form of qualitative descriptive, quantitative analysis for the level of business feasibility, and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The brown cane sugar industry in the past year has been producing for 238 days/year which requires 15 tons/day of raw sugar cane materials. The revenue obtained from pattern I was IDR 4.027.873/day of production, pattern II was IDR 3.252.623/day of production, and pattern III was IDR 3.351.373/day of production. The BEP calculation in pattern I was IDR 2.617.072/day of production or 292,5 kg, BEP pattern II was IDR 2.698.287/production day or 307 kg, and BEP pattern III was IDR 2.779.504/production day or 321 kg. The SWOT analysis was conducted using analysis of internal and external factors that produces several strategies. Several alternative strategies produced are increasing the production volumes, expanding the marketing reach, forming joint business groups, determining the product distribution schedules, using the appropriate technology, utilizing information technology to promote the products, and managing the business licensing.